2021
DOI: 10.1016/j.tcsw.2021.100064
|View full text |Cite
|
Sign up to set email alerts
|

In vitro efficacy of relebactam versus avibactam against Mycobacterium abscessus complex

Abstract: Infections resulting from Mycobacterium abscessus are increasing in prevalence worldwide, with the greatest risk posed to patients with underlying respiratory conditions. Treatment for infections is difficult due to wide ranging intrinsic antimicrobial resistance, which is compounded by the existence of a range of subspecies within the M. abscessus complex, each with varying additional antimicrobial resistance profiles. Previously, the use of β-lactam/β-lactamase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Although the currently available dose/ratio of imipenem/relebactam was optimized, no combination of ceftazidime/avibactam was effective. However, triple-combination imipenem, relebactam, and meropenem resulted in the lowest MICs and minimum bactericidal concentrations for all three subspecies [ 89 ]. Other studies have shown that the addition of ampicillin to imipenem/relebactam, and to a lesser extent to ceftazidime/avibactam, can result in lower Mabs MICs [ 89 , 90 ].…”
Section: Emerging Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the currently available dose/ratio of imipenem/relebactam was optimized, no combination of ceftazidime/avibactam was effective. However, triple-combination imipenem, relebactam, and meropenem resulted in the lowest MICs and minimum bactericidal concentrations for all three subspecies [ 89 ]. Other studies have shown that the addition of ampicillin to imipenem/relebactam, and to a lesser extent to ceftazidime/avibactam, can result in lower Mabs MICs [ 89 , 90 ].…”
Section: Emerging Treatmentsmentioning
confidence: 99%
“…However, triple-combination imipenem, relebactam, and meropenem resulted in the lowest MICs and minimum bactericidal concentrations for all three subspecies [ 89 ]. Other studies have shown that the addition of ampicillin to imipenem/relebactam, and to a lesser extent to ceftazidime/avibactam, can result in lower Mabs MICs [ 89 , 90 ]. Currently, all three β-lactamase inhibitors are available only in coformulations with β-lactams: imipenem/cilastatin with relebactam, ceftazidime with avibactam, and meropenem with vaborbactam.…”
Section: Emerging Treatmentsmentioning
confidence: 99%
“…49 The success of these dual combinations has facilitated investigations of even further complexity, with triple combinations also showing great promise. Successful examples include the following: durlobactam and amoxicillin with either imipenem or cefuroxime 45 ; meropenem and imipenem with avibactam or relebactam 54 ; and imipenem, relebactam and amoxicillin. 55 The possibility for different combinations is therefore extensive and provides an optimistic view for the future of M. abscessus treatment, allowing us to simultaneously increase drug susceptibility and reduce dose requirements to ultimately lessen the treatment burden caused by their side effects.…”
Section: The Future For Antibiotic Combinationsmentioning
confidence: 99%